Forensic Linguistics Study: Online Hate Speech On Social Media Instagram (Indonesian Government) - Elisabeth Dwi Clara; Bertaria Sohnata Hutauruk; Melda Veby Ristella Munthe (Jurnal Ilmu Sosial dan Humaniora, 2026)
The increasing use of social media as a public communication space has led to the widespread emergence of hate speech, particularly in Instagram comment sections related to government issues. This research aims to analyze manifestations of hate speech through illocutionary acts on the Instagram accounts @presidenrepublikindonesia and @kemensetneg_ri, classify their forms based on the National Police Chief’s Circular Letter No. SE/06/X/2015, and identify the most dominant types found in the data. This research employs a qualitative descriptive approach supported by quantitative analysis. The data consists of 200 Instagram comments collected from posts related to public policy and government activities. Analysis was conducted using a pragmatic approach based on illocutionary acts, specifically expressive, directive, and assertive acts as proposed by John Searle, and further classified into categories of hate speech such as insults, defamation, and provocation. The results of the research indicate that expressive speech acts are the most dominant, suggesting that users primarily express negative emotions such as anger, disappointment, and sarcasm. In terms of hate speech classification, insults emerged as the most frequent category, followed by defamation and provocation. Although most of the statements do not fully meet the legal criteria under the ITE Law, they still have the potential to cause negative effects in digital communication. These findings indicate that the line between criticism and hate speech remains unclear among social media users and highlight the importance of understanding language use in a digital context.